SISTEM PENUNJANG KEPUTUSAN PEMILIHAN SISWA BERPRESTASI MENGGUNAKAN METODE WEIGHTED PRODUCT (STUDI KASUS :SMA MUHAMMADIYAH KECAMATAN KATINGAN TENGAH) - Widiatry, Widiatry; Sari, Nova Noor Kamala; Ananingtyas, Arifatul (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2018)
The selection of outstanding students at SMA Muhammadiyah in Central Katingan Districtis conducted to appreciate the excellent students in order to be more motivated and activein learning activities. Building a website-based information system can apply the waterfallmethod and Weighted Product Method (WP) in its manufacture. The software developmentmethod used in making the support system for the students selection is the weighted productmethod (case study: SMA Muhammadiyah in Central Katingan District) . This waterfallmethod according to Sommerville (2011) includes 5 (five) stages namely requirementdefinition, system and software design, implementation and unit testing, integration andsystem settings, operation and maintenance.Application testing is conducted using the blackbox testing method, where the results of thetest can see that the overall website-based decision support system is functions properly.However, it is expected that this application can continue to be developed and optimized forits use in the future, especially in terms of available features.